2016
DOI: 10.6018/analesps.32.3.261671
|View full text |Cite
|
Sign up to set email alerts
|

Promoción de la resiliencia en niños con sintomatología depresiva

Abstract: Título: Promoción de la resiliencia en niños con sintomatología depresiva. Resumen: Se llevó a cabo un estudio experimental con el objetivo principal de estudiar la eficacia de una intervención cognitivo-conductual inspirada en el Programa de Resiliencia de Pensilvania (PRP; Gillham, Jaycox, Reivich, Seligman y Silver, 1990; Seligman, Reivich, Jaycox y Gillham, 2005), como prevención de la depresión infantil en población escolar de Educación Primaria. Los componentes principales del programa son la modificació… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 40 publications
0
1
0
1
Order By: Relevance
“…Though the mean effects were significant they were small: g = 0.11 at outcome and 0.21 at follow-up. A program based on the Penn Resilience Program also found the treatment effective for depression compared to control in a pilot study involving Spanish-speaking youth (Sanchez et al, 2016). Another source of evidence comes from longitudinal research that has demonstrated self-reported resilience predicts the development of mental health problems in high-stress work situations (Wild et al, 2016).…”
Section: Meaningfulnessmentioning
confidence: 99%
“…Though the mean effects were significant they were small: g = 0.11 at outcome and 0.21 at follow-up. A program based on the Penn Resilience Program also found the treatment effective for depression compared to control in a pilot study involving Spanish-speaking youth (Sanchez et al, 2016). Another source of evidence comes from longitudinal research that has demonstrated self-reported resilience predicts the development of mental health problems in high-stress work situations (Wild et al, 2016).…”
Section: Meaningfulnessmentioning
confidence: 99%
“…Pareja (Cienfuegos & Díaz-Loving, 2010) es una escala que ha sido utilizada en varios estudios (Cienfuegos, 2014;Méndez, 2014;Sánchez & Méndez, 2015). El Conflict Tactic Scale -2 (Straus et al, 1996), ha sido una escala ampliamente utilizada desde su publicación, aunque la versión traducida al español (Graña et al, 2013) muestra resultados de confiabilidad menores en todas las escalas, así como la correlación entre las subescalas (Ver tabla 1).…”
Section: Introductionunclassified